2006
DOI: 10.1002/pam.20226
|View full text |Cite
|
Sign up to set email alerts
|

School choice, racial segregation, and test‐score gaps: Evidence from North Carolina's charter school program*

Abstract: Using panel data that track individual students from year to year, we examine the effects of charter schools in North Carolina on racial segregation and black-white test score gaps. We find that North Carolina's system of charter schools has increased the racial isolation of both black and white students, and has widened the achievement gap. Moreover, the relatively large negative effects of charter schools on the achievement of black students is driven by students who transfer into charter schools that are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
204
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(215 citation statements)
references
References 19 publications
9
204
2
Order By: Relevance
“…However, some authors have found that charter schools increase racial segregation (Bifulco & Ladd, 2007) and the potential to further stratify schools along racial and socioeconomic profiles, allowing a mechanism to escape racial integration (Cobb & Glass, 1999). Sohoni and Saporito (2009) examine levels of racial segregation in private, charter, and magnet schools.…”
Section: Preferences For Race/ethnicity and The Socioeconomic Composimentioning
confidence: 99%
“…However, some authors have found that charter schools increase racial segregation (Bifulco & Ladd, 2007) and the potential to further stratify schools along racial and socioeconomic profiles, allowing a mechanism to escape racial integration (Cobb & Glass, 1999). Sohoni and Saporito (2009) examine levels of racial segregation in private, charter, and magnet schools.…”
Section: Preferences For Race/ethnicity and The Socioeconomic Composimentioning
confidence: 99%
“…For example, in several studies, Black students attended charter schools where the percentage of Black students was 15 or more percentage points greater than the TPS they exited Weiher & Tedin, 2002). Additionally, studies of individual charter movers in Arizona (Garcia, 2008), North Carolina (Bifulco & Ladd, 2007), Texas and California (Booker, Zimmer, & Buddin, 2005), and Ohio (Zimmer et al, 2009) support the claim that students-especially Black students-tend to leave more racially diverse TPSs for more segregated charter schools. Some studies also find that White students' transfers to charter schools are also segregative (Zimmer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At a time of persisting neighborhood segregation, it is critical to assess how student movement to and from charter schools affects school segregation, as well as whether students and parents make these choices while more integrative options exist. Few studies have been able to ascertain how movements to charter schools affect segregation, but those that have suggest that the moves to charter schools for Black students result in more segregated school contexts; findings for White and Latino students, where studied, are more mixed (Bifulco & Ladd, 2007;Kotok, Frankenberg, Schafft, Fuller, & Mann, 2015;Stein, 2015;Zimmer et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords: school vouchers, student achievement, program evaluation, attrition Student selection is one of the most controversial aspects of school choice policy. The literature has given prominent attention to the characteristics of students who select into various alternatives to traditional public schools (Betts & Fairlie, 2001;Bifulco & Ladd, 2007;Campbell, West, & Peterson, 2005;Fairlie & Resch, 2002;Figlio, 2008;Figlio, Hart, & Metzger, 2010;Figlio & Stone, 2001;Goldring & Phillips, 2008;Howell, 2004;Lankford & Wyckoff, 2001;Long & Toma, 1988). Accounting for systematic student selection processes is critical for obtaining internally valid estimates of the effect of school choice programs on educational outcomes.…”
Section: Few School Choice Evaluations Consider Students Who Leave Sumentioning
confidence: 99%